Managing international knowledge flows at the fuzzy front end of discontinuous innovation - Neukam, Marion; Guittard, Claude (Management international / International Management / Gestiòn Internacional, 2023)
Spatially distributed knowledge in MNCs presents a challenge for the emergence of discontinuous innovations. Our study suggests that a firm’s ability to efficiently exploit international knowledge during the ‘fuzzy front end’ (FFE) depends on the relationship between international subsidiaries and the rest of the firm. Based on an in-depth case study in an international industrial firm, our empirical work identifies two coordination mechanisms firms can apply to manage their knowledge flows and thus reposition subsidiaries to favor discontinuous innovations: the managerial commitment towards local innovation activities, and the embeddedness of local employees into global innovation processes.